2002
DOI: 10.1007/s00415-002-0884-0
|View full text |Cite
|
Sign up to set email alerts
|

Circadian heart rate variability in Parkinson's disease

Abstract: Parkinson's disease is known to affect the reflex cardiovascular control systems, resulting in a suppressed heart rate variability, but present knowledge concerning the long-term characteristics of heart rate and heart rate variability, e. g. circadian regulation, is limited. We investigated the circadian fluctuation of the time domain, frequency domain and some non-linear measures of heart rate variability in 44 untreated patients with Parkinson's disease and 43 age- and sex-matched control subjects.In the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 32 publications
2
45
0
3
Order By: Relevance
“…Actigraphy studies show increased levels of nocturnal motor activity and an increased proportion of time with movement in PD patients (van Hilten et al, 1994), which suggests a more disturbed sleep as well as a lower amplitude rest-activity rhythm with increased intradaily variability as compared to healthy adults (Whitehead et al, 2008). Moreover, PD patients exhibit alterations in various circadian patterns, such as in melatonin (Bordet et al, 2003) and cortisol (Hartmann et al, 1997) secretion, core body temperature (Bordet et al, 2003;Pierangeli et al, 2001), and heart rate variability (Pursiainen et al, 2002), among others.…”
Section: Introductionmentioning
confidence: 95%
“…Actigraphy studies show increased levels of nocturnal motor activity and an increased proportion of time with movement in PD patients (van Hilten et al, 1994), which suggests a more disturbed sleep as well as a lower amplitude rest-activity rhythm with increased intradaily variability as compared to healthy adults (Whitehead et al, 2008). Moreover, PD patients exhibit alterations in various circadian patterns, such as in melatonin (Bordet et al, 2003) and cortisol (Hartmann et al, 1997) secretion, core body temperature (Bordet et al, 2003;Pierangeli et al, 2001), and heart rate variability (Pursiainen et al, 2002), among others.…”
Section: Introductionmentioning
confidence: 95%
“…HRV indexes in time and cardiac frequency domains have proven useful measures in predicting cardiac arrhythmias, mortality risk by cardiac artery disease and various central nervous system disturbs, such as stroke, epilepsy, brain damages and other degenerative brain disease [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the early stages of PD, patients exhibit a dysregulation in autonomic cardiovascular control as indicated by decreased cardiac radioiodinated metaiodobenzylguanidine uptake, and decreased heart rate variability (Awerbuch and Sandyk 1994;Oka et al 2006). Other studies have confirmed that parasympathetic cardiovascular regulation is impaired in untreated patients with PD, and showed that the dysfunction is more pronounced at night (Pursiainen et al 2002). The location of Lewy bodies is also consistent with ANS pathology in PD; Lewy bodies are found in parasympathetic (dorsal, vagal, and sacral nuclei) and sympathetic (intermediolateral nucleus of the thoracic cord and sympathetic ganglia) control regions (Wakabayashi and Takahashi 1997).…”
Section: Ans Dysfunction In Neurodegenerative and Psychiatric Disordersmentioning
confidence: 69%